2009
DOI: 10.1007/s11845-009-0284-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of transthoracic echocardiography in embolic acute limb ischaemia

Abstract: Transthoracic echocardiography seldom identifies a cardiac embolic source, but identifies many patients with severe incidental cardiac abnormalities, suggesting cardiology screening of these patients remains important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Our data on embolectomy outcomes are similar to those in the literature, including studies dealing primarily with UE, 1,3,9,10 LE 11 and UE and LE 1214 emboli. As noted, atrial fibrillation is a universally recognized risk factor.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our data on embolectomy outcomes are similar to those in the literature, including studies dealing primarily with UE, 1,3,9,10 LE 11 and UE and LE 1214 emboli. As noted, atrial fibrillation is a universally recognized risk factor.…”
Section: Discussionsupporting
confidence: 81%
“…The frequent need for fasciotomies and the approximately 5-15% amputation rate have been reported by others. [12][13][14] In contrast, the need for fasciotomies and amputations is rare in UE emboli. None was required in our series.…”
Section: Discussionmentioning
confidence: 99%
“…TTE also remains a powerful tool to address other incidental cardiac findings. One study demonstrated that TTE used for investigation of ALI revealed that 19% of patients had significant cardiac abnormalities—including severe valvular lesions, systolic dysfunction and ventricular aneurysm 18 . This may also explain why patients hospitalised for ALI have higher subsequent MACE (major adverse cardiovascular events) and all‐cause mortality 12 …”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that TTE used for investigation of ALI revealed that 19% of patients had significant cardiac abnormalities-including severe valvular lesions, systolic dysfunction and ventricular aneurysm. 18 This may also explain why patients hospitalised for ALI have higher subsequent MACE (major adverse cardiovascular events) and all-cause mortality. 12 Given significant atherosclerotic disease was the most common precipitant of ALI (54%), it would be prudent to exclude proximal large-vessel disease with CT angiography, and indeed, this is usually performed by the vascular surgeon.…”
Section: Cardiac Imagingmentioning
confidence: 99%
“…Most commonly the cause is embolic or thrombotic [13,14]. The Rutherford classification [15] provides a common language when discussing severity of acute and chronic limb ischaemia.…”
Section: Acute Lower Limb Ischaemiamentioning
confidence: 99%